Mother tongue classes: A parental choice, but does choice equate with parental involvement and engagement in learning? - Kirk P.H. Sullivan; Annika E. Sjölander (University of Aberdeen, School of Education, 2019)
In Sweden, all children who speak a language other than Swedish at home have a right to mother tongue classes when there are five children in the municipality who request the language as a mother tongue class. This paper reports on ongoing research that is investigating parental involvement and engagement in their children's learning of their mother tongue language. Even though mother tongue classes require an active parental choice and the filling in of an application form, some children drop out of their mother tongue classes claiming the classes are boring and uninteresting, and teachers find that some children do not meet the requirement of using the language as an active home language. Through examination of young learner and school-aged students' mother tongue provision and prompted reflection with parents, we tease apart the elements of agency necessary for parents to feel involved and engaged in their children's mother tongue lessons.